Does Antiretroviral Therapy Packaging Matter? Perceptions and Preferences of Antiretroviral Therapy Packaging for People Living with HIV in Northern Tanzania - Muiruri C; Jazowski SA; Semvua SK; Karia FP; Knettel BA; Zullig LL; Ramadhani HO; Mmbaga BT; Bartlett JA; Bosworth HB (Patient Preference and Adherence, 2020)
Charles Muiruri,1– 3 Shelley A Jazowski,1,4 Seleman K Semvua,3 Francis P Karia,3 Brandon A Knettel,2 Leah L Zullig,1,5 Habib O Ramadhani,3,6 Blandina T Mmbaga,2,3 John A Bartlett,2,3 Hayden B Bosworth1,5,7– 9 1Department of Population Health Sciences, Duke University School of Medicine, Durham, NC, USA; 2Duke Global Health Institute, Duke University, Durham, NC, USA; 3Department of Medicine, Kilimanjaro Christian Medical University College, Moshi, Tanzania; 4Department of Health Policy and Management, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 5Center of Innovation to Accelerate Discovery and Practice Transformation (ADAPT), Durham Veterans Affairs Health Care System, Durham, NC, USA; 6Division of Epidemiology & Prevention, Institute of Human Virology, University of Maryland School of Medicine, Baltimore, MD, USA; 7Duke Heart Center Nursing Research Program, School of Nursing, Duke University, Durham, NC, USA; 8Department of Psychiatry and Behavioral Sciences, Duke University, Durham, NC, USA; 9Division of General Internal Medicine, Duke University, Durham, NC, USACorrespondence: Charles MuiruriDepartment of Population Health Sciences, Duke University School of Medicine, 215 Morris Street, Suite 210, Durham, NC 27701, USATel +1 9196603212Email charles.muiruri@duke.eduIntroduction: Despite improvements in treatment (eg, reduction in pill intake), antiretroviral therapy (ART) is dispensed in socially inefficient and uneconomical packaging. To make pills less conspicuous and decrease the risk of being stigmatized, people living with HIV (PLWH) often engage in self-repackaging – the practice of transferring ART from original packaging to alternative containers. This behavior has been associated with ART nonadherence and failure to achieve viral load suppression. While much of the literature on ART packaging has centered around medication adherence, patients stated preferences for ART packaging and packaging attributes that influence the observed ART nonadherence are understudied.Methods: We conducted a qualitative study to elucidate perceptions of ART packaging among PLWH at two large referral hospitals in Northern Tanzania. Interviews were conducted until thematic saturation was reached. Interviews were audio-recorded, transcribed and coded.Results: Of the 16 participants whose data were used in the final analysis, a majority were between 36 and 55 years of age (Mean 45.5 years SD: 11.1), had primary-level education (n=11, 68.8%), were self-employed (n=9, 56.3%), reported that they had self-repacked ART (n=14, 88%), and were taking ART for more than 6 years (n=11, 68.8%). Participants identified three attributes of ART packaging that increased anticipated HIV stigma and prompted self-repackaging, including visual identification, bulkiness, and the rattling noise produced by ART pill bottles.Conclusion: Given the drastic reduction in the number of pills required for HIV treatment, there is an opportunity to not only assess the cost-effectiveness of innovative ART packaging but also evaluate the acceptability of such packaging among PLWH in order to address stigma and improve ART adherence.Keywords: antiretroviral therapy packaging, HIV, qualitative research, self-packaging, stigma